Edukasi pencegahan kekurangan energi kronik (KEK) pada ibu hamil - Rilyani, Rilyani; Prayoga, Andes; Avifah, Avifah; Ramadhan, Defri Wan; Agnesta, Desvia Ratin; Astuti, Evi; Erwan, Fragesta; Andani, Meri; Amartya, Salsa Ananstasya; Setiawan, Shandi; Usman, Irindy Inayah; Dari, Ulan; Nasta, Beatrick Rosali; Aulia, Devita; Utami, Julia Tri; Sari, Putri Melinda (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Pregnant women need adequate nutrition to stay healthy. This is achieved by increasing and varying the food they consume, but avoiding excessive portion sizes or restricting their diet, as this can harm the fetus. Chronic Energy Deficiency (CED) is a condition in which a pregnant woman experiences a prolonged (yearly or chronic) lack of food, resulting in health problems such as an inability to meet increased nutritional needs during pregnancy. Pregnant women with CED have a higher risk of giving birth with low birth weight (LBW) compared to pregnant women without CED. Purpose: To provide education to increase pregnant women's knowledge about how to prevent and manage CED. Method: This activity was conducted on November 29, 2024, at 9:30 a.m. Western Indonesian Time (WIB) at the Simpur Community Health Center (Puskesmas) in Bandar Lampung. A total of 24 pregnant women and mothers with toddlers attended the activity to serve as respondents. The goal of this activity was health education to increase pregnant women's knowledge regarding the prevention of chronic energy deficiency during pregnancy. Respondent knowledge was measured using a questionnaire administered before the educational activity (pre-test) and after the educational activity (post-test). Evaluation was conducted by asking respondents questions about the explanation and observing changes in their knowledge levels based on the questionnaire results between before and after the educational activity. Results: Data obtained showed that the level of knowledge of respondents before the educational activity was 4 (16.7%) in the good category, 12 (50.0%) in the adequate category, and 8 (33.3%) in the poor category. Meanwhile, the level of knowledge after the educational activity was 16 (66.7%) in the good category, 8 (33.3%) in the adequate category, and no respondents had poor knowledge. Conclusion: This educational activity successfully increased the knowledge and awareness of pregnant women regarding the importance of preventing and managing chronic energy deficiency (CED). Increased knowledge among pregnant women will minimize the risk of CED, thereby improving the health and nutritional quality of pregnant women, which will contribute to achieving the national goal of reducing stunting and maternal mortality. Suggestion: Community Health Centers (Puskesmas) are expected to improve and optimize the implementation of education on the prevention of chronic energy deficiency (CED) for pregnant women in a structured, sustainable, and individual-based manner. Program support that involves the family as a support system for pregnant women is needed to improve adherence to nutritional recommendations. Keywords: Chronic energy deficiency; Health education; Pregnant women; Prevention Pendahuluan: Ibu hamil memerlukan nutrisi agar tetap sehat. Ini dilakukan dengan menggunakan perbanyak dan variasikan makanan yang dikonsumsinya, namun jangan menambah ukuran porsinya dan juga membatasi pola makan karena dapat membahayakan janin dalam kandungan. Defisiensi Energi Kronis adalah suatu keadaan dimana seorang ibu hamil mengalami kekurangan makanan dalam jangka waktu yang lama (menahun atau menahun), sehingga menimbulkan gangguan kesehatan seperti tidak mampu memenuhi peningkatan kebutuhan gizi selama kehamilan. Ibu hamil yang menderita KEK memiliki risiko lebih tinggi untuk melahirkan dengan berat badan lebih rendah (BBLR) dibandingkan ibu hamil tanpa KEK. Tujuan: Memberikan edukasi untuk meningkatkan pengetahuan ibu hamil mengenai cara pencegahan dan penanganan KEK. Metode: Kegiatan ini dilaksanakan pada tanggal 29 November 2024 pada pukul 09.30 WIB di Wilayah Kerja Puskesmas Simpur Bandar Lampung. Sebanyak 24 ibu hamil dan ibu yang memiliki balita menghadiri kegiatan untuk menjadi responden. Sasaran dalam kegiatan ini adalah pendidikan kesehatan untuk meningkatkan pengetahuan ibu hamil mengenai pencegahan kejadian kekurangan energi kronik selama menjalani kehamilan. Pengukuran pengetahuan responden menggunakan kuesioner yang diberikan sebelum kegiatan edukasi (pre-test) dan setelah kegiatan edukasi (post-test). Evaluasi dilakukan dengan mengajukan pertanyaan kembali mengenai isi penjelasan kepada responden dan melihat perubahan tingkat pengetahuan berdasarkan hasil kuesioner antara sebelum kegiatan edukasi dan setelah kegiatan edukasi. Hasil: Mendapatkan data bahwa tingkat pengetahuan responden sebelum kegiatan edukasi adalah sebanyak 4 (16.7%) dalam kategori baik, sebanyak 12 (50.0%) dalam kategori cukup, dan sebanyak 8 (33.3%) dalam kategori kurang. Sedangkan tingkat pengetahuan setelah kegiatan edukasi menjadi sebanyak 16 (66.7%) dalam kategori baik, sebanyak 8 (33.3%) dalam kategori cukup, dan tidak ada responden yang memiliki pengetahuan kategori kurang. Simpulan: Kegiatan edukasi ini berhasil meningkatkan pengetahuan dan kesadaran ibu hamil tentang pentingnya pencegahan dan penanganan gangguan kurang energi kronik (KEK). Peningkatan pengetahuan ibu hamil akan meminimalkan risiko KEK sehingga peningkatan derajat kesehatan dan kualitas gizi ibu hamil akan berkontribusi dalam pencapaian tujuan nasional yaitu menurunkan angka stunting dan angka kematian ibu. Saran: Diharapkan agar Puskesmas dapat meningkatkan dan mengoptimalkan pelaksanaan edukasi pencegahan kekurangan energi kronik (KEK) pada ibu hamil secara terstruktur, berkesinambungan, dan berbasis kebutuhan individu. Diperlukan dukungan program yang melibatkan keluarga sebagai sistem pendukung ibu hamil guna meningkatkan kepatuhan terhadap anjuran gizi.